2008
DOI: 10.1186/1471-2415-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Greek version of the NEI-VFQ 25

Abstract: Background: To evaluate the reliability and construct validity of a Greek version of the NEI-VFQ-25 in patients with chronic ophthalmic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 35 publications
(34 reference statements)
3
61
0
4
Order By: Relevance
“…This is consistent with the work of Massof 18,19 and Massof and Ahmadian, 20 who showed that a subset of NEI VFQ functioning items taps the same construct as other visual functioning instruments; that is, the Visual Functioning 14 (VF-14), the Visual Activities Questionnaire, and the Activities of Daily Vision Scale (ADVS). Many other studies 38,39,55 applied Rasch analysis to the NEI VFQ, but simply to derive Rasch estimates of total and subscale scores. No attempt was made to assess the validity of the NEI VFQ within the Rasch model.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is consistent with the work of Massof 18,19 and Massof and Ahmadian, 20 who showed that a subset of NEI VFQ functioning items taps the same construct as other visual functioning instruments; that is, the Visual Functioning 14 (VF-14), the Visual Activities Questionnaire, and the Activities of Daily Vision Scale (ADVS). Many other studies 38,39,55 applied Rasch analysis to the NEI VFQ, but simply to derive Rasch estimates of total and subscale scores. No attempt was made to assess the validity of the NEI VFQ within the Rasch model.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to the NEI VFQ-39 and the NEI VFQ-25; for the sake of clarity, regardless of the number of items in the revised scales, the revised scales will be identified by their origin as [scale name] 39 or [scale name] 25 . 39 The first revision of the NEI VFQ-39 visual functioning scale was the long-form visual functioning scale 39 (LFVFS 39 ). Following are the details:…”
Section: Phase 2: Reengineering the Nei Vfqmentioning
confidence: 99%
See 2 more Smart Citations
“…36,37 Studies agree that the domains affected greater in glaucoma subjects are mainly general health, general vision, mental health, expectations, driving and near activities both for NEI-VFQ and NEI-VFQ 25 questionnaires. 2,24,33,[38][39] Both tools are shown to be capable of distinguishing glaucoma from normal control subjects, with the scores of glaucoma patients being significantly poorer on most subscales. In addition, lower scores correlated well with visual field loss of glaucoma patients in the eye with the least visual field deterioration.…”
Section: The National Eye Institute Visual Function Questionnaire -51mentioning
confidence: 99%